Amplified spontaneous emission from single CdS nanoribbon with low symmetric cross sections - Zou, Bing Suo (2013)
CdS nanoribbons with various cross sections offer the opportunity to deeply understand the interaction between optical cavity and spontaneous emission. Herein, long tapered nanoribbons with the cross sections gradually changing were synthesized by a simple physical vapour deposition method. Morphology dependent micro-region photoluminescence (PL) spectroscopy is employed to show Purcell effect along different low symmetry cross sections. Spikes on the PL spectra reveal that local density of optical modes increases when the mode match happens between optical cavity and spontaneous emission. Bound exciton complex related amplified spontaneous emission is observed in a single CdS nanoribbon with well-defined elliptical cross sections and optimized width/thickness ratio [similar]1.45. Polarized Raman and TEM confirmed that the nanoribbon with the elliptical cross section adopts the [0002] growth direction with good quality. The results suggest that the cross section resonant cavity would be of importance for both fundamental and practical application of cavity quantum electrodynamics in CdS nanoribbon.